Cluster Promotion with the “Joint Task Program”: An Evaluation of the Concept and its Implementation in Eastern Germany - Wurpts, Klaus; Kirchgeorg, Manfred (Raumforschung und Raumordnung | Spatial Research and Planning, 2013)
Across almost the entire globe, cluster and networking organisations are being supported at a number of administrative levels to boost regions’ economic competitiveness. Within the framework of the program “Joint Task to Improve the Regional Economic Structure”, launched by the Federal Ministry of Economics and Technology, fifty-two of these organisations exist in Eastern Germany alone. In view of their number, and the fact that many of them have already received promotion twice, or the maximum number of times possible, the funding program and its implementation are now being evaluated in this study—against the background of a scientific critique of the cluster concept and its promotion, as well as the absence of publicly accessible evaluations. Findings reveal a lack of thematic and geographical co-ordination, no evaluation of the promotion provided, and an absence of service orientation among the organisation management.